Mali : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
Mali has been implementing reforms supported by the IMF through the Enhanced Structural Adjustment Facility (ESAF) and Poverty Reduction and Growth Facility (PRGF) arrangements. Executive Directors commended the macroeconomic management, poverty reduction, and structural reforms, and emphasized the need for strengthening fiscal performance, the finance system, and the effectiveness of the Anti-Money Laundering and Combating Financing of Terrorism regime. They agreed that the ex post assessment of performance under the (ESAF)/PRGF arrangements have helped Mali to stabilize the macroeconomic situation and improve the structure of its economy.